Effectiveness of residual stress and pores on the β-grain refinement in L-PBF Ti6Al4V processed with hot isostatic pressing - Vivek K Sahu; Hector R. Siller; M.H. Herman Shen (Additive Manufacturing Letters)
The present study examines the effect of HIP (Hot Isostatic Pressing) treatment above the β-transus temperature on porosity reduction and its effect on the transition from columnar to equiaxed prior β-grains in L-PBF (Laser Powder Bed Fusion) Ti6Al4V. HIP treatment was conducted at a holding temperature of 1050 °C and a pressure of 120 MPa for 2 h on the L-PBF Ti6Al4V samples, which were deposited with four different scanning speeds of 300 mm/s, 400 mm/s, 650 mm/s, and 1100 mm/s, while keeping the other deposition parameters constant. The sample with the higher scanning speed (1100 mm/s) exhibits the highest area fraction of lack-of-fusion defects, leading to more pronounced equiaxed β-grain refinement and texture weakening compared to the sample that has the lowest scanning speed (300 mm/s) and negligible lack-of-fusion defect. During the HIP treatment, the local stresses around the sharp tips of the defects, along with the inherent residual stresses in the as-built samples, contribute to the dynamic recrystallization below and above the β-transus temperature.